Kinetic analysis reveals successive steps leading to miRNA‐mediated silencing in mammalian cells - Béthune, Julien; Artus-Revel, Caroline; Filipowicz, Witold (EMBO reports, 2012)
MicroRNAs (miRNAs) regulate most cellular functions, acting by posttranscriptionally repressing numerous eukaryotic mRNAs. They lead to translational repression, deadenylation and degradation of their target mRNAs. Yet, the relative contributions of these effects are controversial and little is known about the sequence of events occurring during the miRNA‐induced response. Using stable human cell lines expressing inducible reporters, we found that translational repression is the dominant effect of miRNAs on newly synthesized targets. This step is followed by mRNA deadenylation and decay, which is the dominant effect at steady state. Our findings have important implications for understanding the mechanism of silencing and reconcile seemingly contradictory data. There is a Hot off the Press (August 2012) associated with this Scientific Report.